2020
DOI: 10.1186/s13049-020-0709-0
|View full text |Cite
|
Sign up to set email alerts
|

Rescue under ongoing CPR from an upper floor: evaluation of three different evacuation routes and mechanical and manual chest compressions: a manikin trial

Abstract: Background: If transport under ongoing cardiopulmonary resuscitation (CPR) from an upper floor is indicated, the ideal CPR-method and evacuation route is unknown hitherto. We aimed to elaborate a strategy for evacuation of patients under ongoing CPR from an upper floor, comparing three different evacuation routes and manual and mechanical chest compressions. Methods: A CPR-training manikin recording CPR-quality was placed on the fifth floor and was evacuated to an ambulance via lift, turntable ladder, or stair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 19 publications
(18 reference statements)
0
11
0
Order By: Relevance
“…A further seven articles were removed after review of full texts. Finally, 23 articles were included in the scoping review [ 4 , 5 , 6 , 7 , 8 , 11 , 12 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. The characteristics of included studies are summarised in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…A further seven articles were removed after review of full texts. Finally, 23 articles were included in the scoping review [ 4 , 5 , 6 , 7 , 8 , 11 , 12 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. The characteristics of included studies are summarised in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Since this was not the case in the CPR-S group, the recommended average compression depth was achieved; this finding aligned with the results of studies conducted by Shinchi et al 12 and Jansen et al 13 An effective CPR depth was achieved using CPR-MCCD; this was also reported in a manikin study by Gassler et al 9 The study compared the effectiveness of the various types of MCDD and manual CPR while transporting patients on a helicopter. 9 A manikin study by Drinhaus et al 14 compared the effectiveness of MCDD and manual CPR methods while transporting patients on a stretcher. Since there were no significant differences between the CPR-S and CPR-MCDD groups, the CPR-S method was found to be as effective as the CPR-MCDD group, especially in terms of compression depth.…”
Section: Discussionmentioning
confidence: 99%
“…Transport situations using mCPR devices that have been investigated to date primarily include ambulance, turntable ladders and helicopter transport [17][18][19][20]. In the study by Lyon et al, use of a soft stretcher with AutoPulse achieved good results and was presented as a possibility for improved rescue measures [21].…”
Section: Discussionmentioning
confidence: 99%